Peritraumatic distress among emergency medical system employees: A proposed cut-off for the Peritraumatic Distress Inventory - Beata Rybojad; Anna Aftyka; Joanna Milanowska (Annals of Agricultural and Environmental Medicine, 2019)
Introduction Emergency medical system (EMS) workers are exposed to traumatic events that may lead to posttraumatic stress disorder (PTSD).